ANALYSIS OF THE USE OF LOCUTIONARY, ILLOCUTIONARY, AND PERLOCUTIONARY SPEECH ACTS IN INDONESIAN LANGUAGE LEARNING AT SENIOR HIGH SCHOOLS - Abd. Rahim (Sean Institute, 2022)
Actions that take place through the medium of language are called speech acts. In the field of pragmatics, speech acts play a key function. This investigation is concerned with the problem of how students in grade 11 at SMA Tunas Dharma Karawang learn Indonesian from their teachers, specifically focusing on the form and purpose of the teacher's speech actions. This research intends to characterize locutionary, illocutionary, and perlocutionary speech acts as they are used in Indonesian language SMA Tunas Dharma Karawang class XI. Qualitative research methods are used in this study. Instructors and students in Indonesian 11 at SMA Tunas Dharma Karawang constituted the subjects of the study. Methods of gathering information, such as open-ended listening and conversation, making notes, and jotting down observations. The method of data analysis is functionally equivalent. These findings from the study can be characterized as: uncovered utterances featuring locutionary, illocutionary, and perlocutionary speech acts. News, questions, and commands are all examples of locutionary speech acts. Assertive, directive, expressive, commiserating, and declarative illocutionary acts are all examples of speech acts. The effectiveness of perlocutionary speech acts is found.